2018
DOI: 10.1080/21505594.2018.1514237
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors Rv0081 and Rv3334 connect the early and the enduring hypoxic response of Mycobacterium tuberculosis

Abstract: The ability of Mycobacterium tuberculosis (M. tb) to survive and persist in the host for decades in an asymptomatic state is an important aspect of tuberculosis pathogenesis. Although adaptation to hypoxia is thought to play a prominent role underlying M. tb persistence, how the bacteria achieve this goal is largely unknown. Rv0081, a member of the DosR regulon, is induced at the early stage of hypoxia while Rv3334 is one of the enduring hypoxic response genes. In this study, we uncovered genetic interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…One cell length being very long could be explained by the presence of two dimers in the crystal asymmetric unit arranged in a side‐to‐side manner. Earlier it has been reported that the molecule is likely to be a monomer; however, recently it has been reported that Rv0081 exist in a dimeric form and also forms higher oligomers at higher concentration . Therefore, we tested the presence of dimeric association through multi‐angle light scattering coupled with size‐exclusion chromatography (SEC‐MALS).…”
Section: Resultsmentioning
confidence: 99%
“…One cell length being very long could be explained by the presence of two dimers in the crystal asymmetric unit arranged in a side‐to‐side manner. Earlier it has been reported that the molecule is likely to be a monomer; however, recently it has been reported that Rv0081 exist in a dimeric form and also forms higher oligomers at higher concentration . Therefore, we tested the presence of dimeric association through multi‐angle light scattering coupled with size‐exclusion chromatography (SEC‐MALS).…”
Section: Resultsmentioning
confidence: 99%
“…The number in parentheses indicates the number of genes evaluated in each group. (C) The log2 fold-change distribution of Late hypoxia genes with significant differential expression (P-value < 0.05, absolute log2 fold-change >1) from the ΔRv0081 strain in hypoxia (Sun et al, 2018). (D) Boxplots representing log2 fold-change of various gene groups related to Late hypoxia state from Rv0081 transcription factor overexpression (TFOE) (Rustad et al, 2014).…”
Section: Fig 4 Data Supporting Rv0081-controlled Interlocking Ffls mentioning
confidence: 99%
“…Numbers on top of the dendrogram branches indicate the unbiased P-value (au; black) and bootstrap support (bp; purple) for each branch. T0 T1 T2 T3 T4 T5 T6 T7 T8 T9 T10 T11 T12 T13 T14 T15 T16 T17 T18 T19 T20 T21 T22 T23 T24 T25 T0 T1 T2 T3 T4 T5 T6 T7 T10 T12 T13 T14 T15 T16 T17 T18 T22 T23 T24 T25 T21 T19 T20 T9 T8 T11 T18 T16 T17 T0 T1 T25 T22 T23 T24 T2 T3 T4 T7 T5 T6 T14 T15 T10 T12 T13 0 20 40 60 80 Height 100 100 100 100 100 58 100 62 100 100 100 100 100 100 100 100 100 100 100 100 99 99 99 100 au 100 100 100 100 99 57 100 56 100 100 100 100 100 100 100 100 100 100 Plot is based on the comparison between the normoxic TFOE data and hypoxic ΔRv0081 data (Rustad et al, 2014;Sun et al, 2018). Only genes with differential expression in the Rv0081deletion s...…”
Section: Modeling Of Rv0081-directed I-ffl With Late Hypoxia Gene Expmentioning
confidence: 99%
See 2 more Smart Citations